2017
DOI: 10.1111/ggi.12995
|View full text |Cite
|
Sign up to set email alerts
|

Social participation among older adults not engaged in full‐ or part‐time work is associated with more physical activity and less sedentary time

Abstract: Promoting social participation among older adults could contribute to increasing physical activity and reducing sedentary time, with potential benefits for chronic disease. Further research is required to elucidate the deleterious and beneficial roles of passive and mentally-active sedentary time for older adults. Geriatr Gerontol Int 2017; 17: 1921-1927.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 25 publications
(25 reference statements)
2
49
1
3
Order By: Relevance
“…A study including Japanese elderly found increased social participation to be associated with less leisure‐time SB (males) and passive leisure‐time SB (eg, watching TV) . The accelerometer study by Amagasa et al found that older Japanese who do not drive a personal car accumulated more total SB.…”
Section: Resultsmentioning
confidence: 99%
“…A study including Japanese elderly found increased social participation to be associated with less leisure‐time SB (males) and passive leisure‐time SB (eg, watching TV) . The accelerometer study by Amagasa et al found that older Japanese who do not drive a personal car accumulated more total SB.…”
Section: Resultsmentioning
confidence: 99%
“…Social engagement has been found to be associated with positive health behaviors among older adults [6]. For example, higher levels of social engagement were reported to be positively associated with consuming at least five daily servings of fruit and vegetable and moderate-to-vigorous physical activity [7,8]. Kawachi and Berkman suggested that engaging in social activities promoted healthy behaviors and discouraged unhealthy ones by enhancing psychosocial processes through the provision of emotional support from trusted social networks, such as family, friends, neighbors and community [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although social participation has been shown to be useful for maintaining and improving the health of the elderly, the relationship with sedentary behavior is not fully understood. Kikuchi et al [24] showed that social participation for elderly people was useful in reducing sedentary behavior.…”
Section: Hypothesismentioning
confidence: 99%